In Vitro Sterilization Protocol for Micropropagation of Chimonobambusa jaunsarensis (Gamble) Bahadur and Naithani-A Rare and Endangered Hill Bamboo - Maqbool Rather, M.; Thakur, Ajay; Panwar, Monika; Sharma, S. K. (Indian Forester, 2016)
For obtaining contamination free cultures, the most important step is sterilization of explants. In the present study, the sterilization procedure was standardized for Chimonobambusa jaunsarensis syn. Arundinaria jaunsarensis. Comparison was done between three important sterilants, HgCl2(0.05%, 0.1% and 0.15% w/v) for 5, 10 and 15 minutes; NaOCl (5%, 10% and 15% v/v) for 5, 10 and 15 minutes and H2O2 (5 %, 10% and 15% v/v) for 5, 10 and 15 minutes, supplemented with few drops of Tween 20 per 100 ml. Sterilized explants were inoculated on MS medium supplemented with 1mg/l BAP to evaluate the response of different sterilants. The present study has been done to standardize the sterilization method for explant of chimonobambusa jaunsarensis for in-vitro propagation intended for its propagation using different types of sterilizing agents by varying their concentration and duration of exposure. Result showed that amongst the three sterilants i.e. Mercuric chloride (HgCl2) Sodium hypochlorite (NaOCl), and Hydrogen peroxide (H2O2) HgCl2 was found better for controlling the infection with maximum number of healthy cultures.